2009
DOI: 10.1111/j.1467-6419.2009.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

The Stock Market, Housing and Consumer Spending: A Survey of the Evidence on Wealth Effects

Abstract: Abstract. This paper examines the time-series and micro-econometric evidence on the relationship between stock and house prices and consumer spending. The time-series studies distinguish between short-run and long-run links between consumption, income and wealth. They allow us to identify which variables adjust to restore the long-run equilibrium in the case of a shock, and to determine the time taken by the adjustment process. The micro-econometric literature improves our understanding of the link between wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 67 publications
2
37
0
2
Order By: Relevance
“…However while there is an extensive literature on the effects of property prices or housing wealth on consumption expenditures, (see the surveys by Cooper and Dynan (2016) and Paiella (2009)), there is much less on their effects on household debt. This paper refers to this argument as the housing boom hypothesis (HBH): home buyers take out larger mortgages relative to their income in the face of rapidly rising house prices.…”
Section: Introductionmentioning
confidence: 99%
“…However while there is an extensive literature on the effects of property prices or housing wealth on consumption expenditures, (see the surveys by Cooper and Dynan (2016) and Paiella (2009)), there is much less on their effects on household debt. This paper refers to this argument as the housing boom hypothesis (HBH): home buyers take out larger mortgages relative to their income in the face of rapidly rising house prices.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in stock market wealth can lead to the higher consumption either by households liquidating the appreciated stocks or by consuming the dividend stream that these assets generate, or by increasing the borrowing capacity of liquidity constrained households (Paiella, 2009). The following studies showed that the impact of stock wealth to be much more important than housing wealth to consumption, they are scattered in various countries.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…; an impressive recent survey of time series and micro-econometric evidence on wealth effects is provided by Paiella (2009), itself building on the equally excellent Poterba (2000). The studies most related to the present paper are those that provide evidence for Italy.…”
Section: Introductionmentioning
confidence: 99%